The poetics of epiphany in the Spanish lyric of today - Nantell, Judith (Bucknell University Press, 2019)
Drawing on the poetry of four major voices in the Spanish lyric of today, Judith Nantell explores the epistemic works of Luis Muñoz, Abraham Gragera, Josep M. Rodríguez, and Ada Salas, arguing that, for them, the poem is the fundamental means of exploring the nature of both knowledge and poetry. In this first interpretive analysis of the epistemic nature of their poetry, Nantell innovatively engages these poets, each of whom has contributed one of their own poems along with a previously unpublished explication of their chosen poem. Each also provides an original biographical sketch to support Nantell's development of a poetics of epiphany.